Variational statements of a statical problem of the elasticity theory under the preset external forces - Molchanov , I. N.; Galba , E. F. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
The initial-value problem is considered for the equations of elastic equilibrium of moving bodies when stresses are specified on the surface of the body. Two variational problems that may be solved in unique fashion over the entire space are formulated for this problem, which is known to possess a unique solution in a subspace.